The Process Of Reviewing The Sale And Purchase Of Legal Aspects Of High Heritage Land Disputes (Analysis Of Decision Number : 11/Pdt.G/2015/Pn.Bsk) - Ridho Syahputra Manurung (CV. Inara, 2022)
Land disputes are one of the maximum tough troubles to remedy and need to be dealt with carefully. High inheritance is the not unusual place assets of a folks who are associated through blood and inherited from era to era from their ancestors. Buying and promoting consistent with normal regulation is an alternate and is what's known as coins or coins. The hassle is that layout land (excessive heritage) can not be traded primarily based totally at the West Sumatra Regional Regulation Number 6 of 2008 regarding layout land and its utilization. The formula of the hassle on this thesis is what's protected withinside the putting of the scope consistent with Decision quantity 11/Pdt.G/2015/PN.BSK, what elements are the reasons for excessive inheritance land disputes and the way to remedy excessive inheritance land disputes. sale and buy decided through the Batusangkar District Court. The nature of this thesis study is descriptive studies the use of a qualitative method and the form of normative criminal studies and empirical juridical method (sociology). The records series method makes use of number one records, particularly statement, and secondary records, that is received from legal guidelines and regulations, books, work medical papers associated with these studies, criminal dictionaries, reliable files, and regulations In conclusion, it seems that layout rights (Tanah Pusaka Tinggi) can not be traded, however in fact from the case that I analyzed, selection quantity 11/Pdt.G/2015/PN.Bsk became out to be withinside the normal community, the excessive inheritance land was traded and subsequently have become a dispute that subsequently entered the world of regulation.